The European tributary states of the Ottoman Empire in the sixteenth and seventeenth centuries - Kármán, Gábor 1977-; Kunčević, Lovro (Ottoman Empire and its heritage, 2013)
"The European Tributary States" is the first attempt to give a comprehensive overview of the similarities and differences in the Ottoman Empire's relationship to Moldavia, Wallachia, Transylvania, Ragusa, the Crimean Khanate as well as the Cossack Hetmanate